KEPRIBADIAN ANAK DARI POLA ASUH AUTHORITARIAN DALAM PRESPEKTIF ISLAM - Siti Makhmudah (Universitas Islam Lamongan, 2020)
The problem of children and education is a very interesting problem for an educator and parents who face children who need education all the time. Nurturing and raising a child means caring for his life and health and educating him with full sincerity and affection also also forgive the mistakes of children. Departing from this fundamental reason researchers are interested in discussing further related to this issue in the hope that it can provide educational development going forward. This study aims to determine how the child's personality from authoritarian parenting. This research method uses descriptive qualitative case study approach. The subject of this study was a 10-year-old girl who was in elementary school. The results showed that the authoritarian parenting mother had a great influence on the formation of the child's personality, the child became bolder, easily rebelled and easily influenced, the child must be on the other hand to be disciplined and learn to respect time. The subject of this study was a 10-year-old girl who was in elementary school.